Error Estimates for Barycentric Finite Volumes Combined with Nonconforming Finite Elements Applied to Nonlinear Convection-Diffusion Problems - Dolejsi, Vit; Feistauer, Miloslav; Felcman, Jiri; Klikova, Alice (Applications of mathematics (Prague), 2002)
The subject of the paper is the derivation of error estimates for the combined finite volume-finite element method used for the numerical solution of nonstationary nonlinear convection-diffusion problems. Here we analyze the combination of barycentric finite volumes associated with sides of triangulation with the piecewise linear nonconforming Crouzeix-Raviart finite elements. Under some assumptions on the regularity of the exact solution, the L^sup 2^(L^sup 2^) and L^sup 2^(H^sup 1^) error estimates are established. At the end of the paper, some computational results are presented demonstrating the application of the method to the solution of viscous gas flow.[PUBLICATION ABSTRACT]